The Impact of derivatives trading on the liquidity of stocks at the Nairobi Securities Exchange - Muthanga, Naomi Wangu (Strathmore University, 2022)
The introduction of derivatives to enhance liquidity of capital markets is an approach that has been adopted both globally and in Africa. In Kenya, CMA granted approval to the NSE to launch and operate NEXT Derivatives Exchange Market which was aimed at facilitating a deeper and more liquid capital market. One of the challenges experienced in the Kenyan financial market is low liquidity levels which has been a constraint towards product and service uptake by investors. This research focused on Single Stock Futures (SSF) for Safaricom Plc, Kenya Commercial Bank Group Plc, Equity Group Holdings Plc, East Africa Breweries Ltd, British American Tobacco Kenya Plc and Absa Bank Kenya PLC.The researcher collected daily share closing price and daily trading volume data for each of the six underlying company stocks from July 4th, 2018, to December 31st, 2021, which was used in the calculation of stock liquidity using the Amihud Price Impact measure considered the best price impact measure of liquidity. A bivariate VAR model containing the variables: liquidity of underlying stock (Ls) and derivatives trading (Ds) was used to test the short run and long run causality between derivatives trading and the liquidity of underlying stocks. This was used to answer the research objective which was to analyze the impact of derivatives trading (Single Stock Futures) on the liquidity of underlying stocks listed at the NSE. The findings of this study show that there was an increase in the liquidity for some of the underlying stocks as measured by the Amihud price impact measure and a decrease in liquidity for some of the underlying stocks six months and one year post derivatives listing. The increase in stock liquidity for Equity Group Holdings Plc can be explained by derivatives trading in the long run and the increase in stock liquidity for East African Breweries Ltd can be explained by derivatives trading in the short run. The increase in stock liquidity can be explained by the increased investment opportunity available to investors through the introduction of derivatives of the underlying stock. Therefore, market regulators like CMA, NSE and NEXT should encourage more companies to participate in the derivatives market increasing the investment opportunities available to investors. Findings of the research also revealed that the derivatives market was operating efficiently since its launch, the relationship between key participants was working effectively, the clearing process was efficient, and the rules and regulations of the derivatives market were sufficient. Finally, investors were keen on participating in the derivatives market which the CMA and NSE can leverage on to increase trading activity at the bourse through the implementation of aggressive campaigns.
A Thesis submitted in partial fulfilment of the requirements for the award of a Master of Commerce Degree in Finance of Strathmore Business School